Novel direct effect of CCR2 receptor on follicle activation process - Yamila Gamaleri; Delfina Sol Ferman; Alison Ting; Alison Ting; Eduardo Raúl Dascal; Alejandro Lomniczi; Juan Pablo Jaworski; Marina Cinthia Peluffo (Frontiers in Endocrinology)
IntroductionThe regulation of primordial follicle activation is crucial for maintaining ovarian function, the duration of the reproductive phase, and fertility in women; therefore, we propose as our general objective to determine the physiological role of the chemokine receptor CCR2 within the follicular activation process.MethodsOvarian cortex fragments from adult domestic cats (Felis catus) were cultured under different experimental groups: control (media alone), CCR2 antagonist (1µM), and recombinant chemokine CC-motif ligand 2 (CCL2) at two concentrations (10 ng/ml and 100 ng/ml) for 4 h or 48 h. At the end of the culture, the fragments were collected for RNA extraction, cDNA synthesis, and quantitative real-time PCR (4 h) or fixed and processed for paraffin embedding (48 h) for hematoxylin and eosin staining or immunohistochemistry for Ki67, bromodeoxyuridine (BrdU) and AKTp.ResultsStimulation of CCR2 significantly increased the normalized mRNA expression of KIT, FOXO3 (10 ng/ml), and AKT (100 ng/ml) compared to the control (p<0,05). Moreover, there was a significant increase in the percentage of transitional follicles (and a decrease in primordial follicles), together with an increase in oocyte diameter compared with the control and the antagonist groups (p<0.05). Also, in the presence of CCL2, a higher proportion of transitional and primary follicles immunolabeled for BrdU and Ki67 (p<0.05), as well as intense AKTp staining in the nucleus and cytoplasm of oocyte and granulosa cells of primordial, transitional and primary follicles, were observed. On the contrary, a lower proportion of BrdU and Ki67-positive follicles were observed in the antagonist group (p < 0,05).ConclusionOur results show a direct effect of the chemokine CCL2 and a role of the CCR2/CCL2 system on the ovarian cortex, suggesting that the CCR2 receptor signaling in the ovarian cortex may regulate events critical for promoting the stimulation of the transition from primordial to primary follicles.